2015
DOI: 10.1097/gme.0000000000000377
|View full text |Cite
|
Sign up to set email alerts
|

Depressed calcium cycling contributes to lower ischemia tolerance in hearts of estrogen-deficient rats

Abstract: Ovariectomy impairs myocardial Ca(2+) removal by increasing the expression of the SERCA2a inhibitor PLB. Defective Ca(2+) transport causes ischemic Ca(2+)(i) overload and insufficient postischemic recovery of Ca(2+)(i) transients, which entail depressed hemodynamic restitution. Protection of intact Ca(2+) cycling in the myocardium by estrogens plays a major role in enhancing IT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 45 publications
2
9
0
Order By: Relevance
“…Diastolic function in the post-ischemic phase is represented by the LVEDP value (i.e., contracture state). In our experiments, contracture was evaluated only after ischemia, although during ischemia an increase of contracture was observed, as reported by Dunay et al (2015). pGlu-Serp infusion before ischemia significantly reduced LVEDP in SHR_pGlu-Serp-Pre group compared to the respective Control counterpart (p<0.05 vs. SHR_Control).…”
Section: Resultssupporting
confidence: 67%
“…Diastolic function in the post-ischemic phase is represented by the LVEDP value (i.e., contracture state). In our experiments, contracture was evaluated only after ischemia, although during ischemia an increase of contracture was observed, as reported by Dunay et al (2015). pGlu-Serp infusion before ischemia significantly reduced LVEDP in SHR_pGlu-Serp-Pre group compared to the respective Control counterpart (p<0.05 vs. SHR_Control).…”
Section: Resultssupporting
confidence: 67%
“…Our results clearly demonstrated that an impairment in cardiac contractile function, including decreased fractional shortening and mitral valve E/A ratio, was observed in estrogen-deprived rats and obese-insulin resistant rats, whereas the impairment of cardiac ]i regulation in either estrogen deprivation condition or obesity alone (Apaijai et al, 2014;Bupha-Intr & Wattanapermpool, 2006;Dunay et al, 2015). However, our current study demonstrates that these deleterious effects were aggravated in obese-insulin resistant rats with estrogen deprivation, that is when both conditions were present.…”
Section: Discussionsupporting
confidence: 55%
“…This aggravation could be due to impairment in the expression of cardiac Ca 2+ handling proteins in obese‐insulin resistant rats with estrogen deprivation. Previous studies have shown that the expression of SERCA protein (Bupha‐Intr & Wattanapermpool, ; Dunay et al, ) and Ca 2+ uptake activities were decreased (Bupha‐Intr & Wattanapermpool, ) in ovariectomized rats. Our results demonstrated that SERCA, NCX and RYR expression were decreased in estrogen‐deprived rats and obese‐insulin resistant rats.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…However, in other studies, no change was observed in the expression of NCX expression in both oestrogen treatment and OVX animals . Although oestrogen decreased the expression of PLB, and OVX increased its expression, no change in expression was found in other reports . On the other hand, oestrogen downregulated the RyR expression, while in other reports both OVX and oestrogen treatments had no effect on RyR expression .…”
Section: Ers and βArs As Coregulators Of Cardiac Ca2+‐handling Proteinsmentioning
confidence: 74%